Ragam Syirik Modern Dalam Pandangan Al-Qur’an - Amiruddin (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2023)
Shirk is a concept in Islam that refers to the act of associating partners with Allah or giving obedience and worship to someone other than Him. Shirk is considered the greatest sin in Islam, because it tarnishes the concept of monotheism or the oneness of Allah. The impact of shirk in the life of a Muslim is very large. Apart from being the biggest sin, shirk can also result in spiritual and moral destruction. Islam teaches that a person's faith will not be accepted if there are elements of shirk in his heart. Therefore, a correct understanding of monotheism and efforts to avoid all forms of shirk are important in a Muslim's religious practice. Shirk in Islam has evolved over time. This article examines the phenomenon of modern shirk, namely the form of shirk that appears in the context of contemporary life. Through a cultural and religious analysis approach, this research explores how the values of materialism, consumerism and technology can become a new form of shirk that emerges in modern society. Apart from that, this article also discusses the impact of modern shirk on the spiritual and moral life of society, as well as efforts to overcome and avoid its spread. By understanding modern shirk, it is hoped that better awareness can be created about the threat of shirk in the current context and provide a basis for prevention and control efforts.